Teachers identifying and responding to learner errors and misconceptions in numbers, operations and relationships in the intermediate phase - Bowers, Beryl Elizabeth (Stellenbosch : Stellenbosch University, 2021)
Thesis (MPhil)--Stellenbosch University, 2021.